A educação de jovens e adultos no município de Assis Chateaubriand: constituição histórica e possibilidades educativas - Tomim, Solange Rodrigues (2019)
Considering the nationally produced productions that portray the history of youth and adult education, the present work deals with this modality of education in the inner city of the State of Paraná, as an educational possibility for adolescents, youths and adults who could not complete basic schooling in time and age. The present research aims to know and understand the main historical facts of the education of young people and adults in the Brazilian educational scenario and parallel to the national scope, as this teaching modality in Assis Chateaubriand was consolidated. To faithfully analyze the main educational programs aimed at youth and adult education in this locality and how they can contribute to the integral formation of people through the process of basic schooling. The methodologies used to carry out the research were documentaries, bibliographies and field interviews with questionnaires and interviews, for students and teachers of Youth and Adult Education, at the State Center for Basic Education for Young and Adult Assis chateaubriand. With this mote of information, the produced text became robust as to the important information that related the historical constitution of this modality of education in that city and region. We also obtained results and disturbing information about the way in which this form of education and care was designed for the young person and the adult, who lived in this municipality, since there were numerous attempts at educational actions in view of the educational reality specific to this type of student as well as the significant number of people residing in the municipality of Assis chateaubriand who still need the basic stage of literacy. We consider at the end of this research that there is still a need to go deeper into the methodological issues of education for young people and adults, as well as the ongoing training of teachers to work in this type of teaching.